2016
DOI: 10.5812/cardiovascmed.31528
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of QT and JT intervals in patients with left bundle branch block

Abstract: BackgroundProlongation of the QT interval is considered a risk factor for cardiac adverse events and mortality. Left bundle branch block (LBBB) lengthens the QT interval. The corrected QT interval (QTc) is most likely overestimated because its prolongation is caused by increases in depolarization duration and not in repolarization.ObjectivesIn this study, we aimed to apply corrected JT interval (JTc) as an appropriate measure of ventricular repolarization for predicting QTc in a formula.Patients and MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…Alizadeh et al also reported improvement in 65% of patients with use of hand grip, and 75% with use of squatting (compared to 43% with the control treatment of increased hydration and salt consumption). While this study was not identified in our original search, it does align with the findings of our meta-analysis (88). During activities of daily living, while many patients do appear to experience relief from CPM use, the current findings are limited by a lack of control or placebo condition (55,65,67,72,89), and a small sample size (57,58,65).…”
Section: Treatment Efficacysupporting
confidence: 68%
“…Alizadeh et al also reported improvement in 65% of patients with use of hand grip, and 75% with use of squatting (compared to 43% with the control treatment of increased hydration and salt consumption). While this study was not identified in our original search, it does align with the findings of our meta-analysis (88). During activities of daily living, while many patients do appear to experience relief from CPM use, the current findings are limited by a lack of control or placebo condition (55,65,67,72,89), and a small sample size (57,58,65).…”
Section: Treatment Efficacysupporting
confidence: 68%
“…Besides the suggestion to evaluate the JT interval in patients with LBBB as an alternative risk-stratification method in the presence of LBBB [1] , several formulas were developed the last years for avertable estimation of the QT interval [14] , [15] , [16] , [17] , [18] , [19] , [20] ( Table 1 ). A different approach in pacemaker recipients is the subtraction of 50 ms of the QTc LBBB as a rule of thumb.…”
Section: Assessing Qt-interval In the Presence Of Bundle-branch Blockmentioning
confidence: 99%
“…Subsequently, several additional formulas followed and were used in a similar way to the prior assessment methods. Like for the development of the Bogossian-formula in 2014, Tabatabaei et al (2016) and Wang et al (2017) used also the method of artificial LBBB during right ventricular pacing in patients who underwent electrophysiological studies [17] , [18] . Finally, Yankelson et al (2018) and Tang et al (2019) used the second assessment-method of the Bogossian-formula and analyzed patients with intermittent LBBB or with LBBB after trans -aortic valve replacement (TAVR) [19] , [20] , [22] .…”
Section: Assessing Qt-interval In the Presence Of Bundle-branch Blockmentioning
confidence: 99%
“… 40 Obviously, the QTc measurement does not make any sense in the presence of complete left bundle branch block and, in such a case, the use of the JTc interval is more appropriate. 20 , 21 , 41 The QRS duration, the transition QRS zone, the electrical left ventricular hypertrophy, and the frontal QRS-T angle are influenced by myocardial mass and fibrosis. Particularly, the QRS duration, a marker of intraventricular conduction, was independently related to all-cause mortality, 42 especially in patients with severe AS and low flow, low gradient and reduced ejection fraction.…”
Section: Discussionmentioning
confidence: 99%